Dual career - tug of war between elite sports and vocational schooling - Ratzlaff, L.; Speer, A.; Wulff, H.; Wagner, P. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Introduction In secondary school settings, dual career support services exist almost exclusively for high school students [1]. For vocational schools, less is known about students` challenges particularly resulting of school-based and vocational education and participation in elite sports (ES). The research project comprises an adjusted curricular framework to promote a dual career at a vocationally-oriented school for the first time nationwide. It includes a two-year extension of school time period and is focused on reducing the double load of requirements. Thus, the aim of the study was to evaluate the curricular framework`s effects on daily school and exercise routines of ES students. Methods Between 2016-2022, N=160 ES students and N=171 regular students participated in evaluation program. Based on annual standardized questionnaires students were asked about their management of time resources, satisfaction with various support services and their academic and sports performance development (1="very dissatisfied" to 6="very satisfied"). Additionally, teachers` and coaches` point of view derived from interviews. All regular students were used as a control group. Data were analyzed descriptively based on mean and standard deviation. To calculate between-group-effects an independent t-test (p<0.05) was used. Results Descriptive analyses resulted that ES students have a higher workload due to athletic training (9.1±0.9 training sessions per week) in addition to daily study time. The organized support service of exemption from lessons was used significantly more by ES students than by the control group (p<0.001) and was rated higher with regard to satisfaction (p=0.007). Furthermore, ES students were "rather satisfied" with school routines (4.6±0.8). At the end of their school time, ES students rated satisfaction with their academic (4.3±1.0) and sports performance (4.4±1.1) development nearly the same. However, there were no significant differences in ratings of satisfaction with academic development between both groups (p=0.964). Overall, ES students were "fairly satisfied" with the extended school time period (5.2±0.9). Discussion Despite the double burden, there is a high level of overall satisfaction among the ES students with their academic and sports performance development. Special support services could help ES students coping with daily requirements at the vocationally-oriented school. The positive evaluation of the school routines reflects the structured organization and implementation of the adjustments in school time. According corona-related experiences, the increased application of digital teaching tools should lead to higher flexibility in everyday school life and support the offer to promote a dual career.